2014
DOI: 10.1037/spq0000071
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the academic problem behaviors of adolescents with ADHD.

Abstract: Objective This study possessed two aims: (1) to develop and validate aclinician -friendly measure of academic problem behavior that is relevant to the assessment of adolescents with ADHD and (2) to better understand the cross-situational expression of academic problem behaviors displayed by these youth. Method Within a sample of 324 adolescents with DSM-IV-TR diagnosed ADHD (age M=13.07, SD=1.47), parent, teacher, and adolescent self-report versions of the Adolescent Academic Problems Checklist (AAPC) were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 62 publications
(115 reference statements)
1
52
0
1
Order By: Relevance
“…One measure recently developed that has parent and teacher versions and that assesses multiple aspects of the homework completion cycle is the Homework Performance Questionnaire (Power et al, 2014). Another measure that broadly assesses the academic behaviors that adolescents with ADHD struggle with including homework behaviors is the Adolescent Academic Problems Checklist (AAPC; Sibley, Altszuler, Morrow, & Merrill, 2014). Both of these measures would appear to be good tools for broadly assessing treatment outcomes with homework focused interventions as they have parent and teacher versions.…”
Section: Discussionmentioning
confidence: 99%
“…One measure recently developed that has parent and teacher versions and that assesses multiple aspects of the homework completion cycle is the Homework Performance Questionnaire (Power et al, 2014). Another measure that broadly assesses the academic behaviors that adolescents with ADHD struggle with including homework behaviors is the Adolescent Academic Problems Checklist (AAPC; Sibley, Altszuler, Morrow, & Merrill, 2014). Both of these measures would appear to be good tools for broadly assessing treatment outcomes with homework focused interventions as they have parent and teacher versions.…”
Section: Discussionmentioning
confidence: 99%
“…The high risk of low school performance associated with attention-deficit hyperactivity disorder (ADHD) is well established (American Psychiatric Association, 2014;DuPaul, Gormley, & Laracy, 2012;Sibley, Altszuler, Morrow, & Merrill et al, 2014). Writing seems to be the most impaired and the least studied skill in this group of children (Mayes & Calhoun, 2006;Dorneles et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents with DSM-IV-TR ADHD ( N = 299) enrolled in one of four concurrent psychosocial treatment studies with a common battery at an ethnically diverse urban university clinic (Sibley et al 2013, 2014a, b, c, 2015a, b). Participants were referred by their parents and schools and data were collected from parents, adolescents, and teachers at initial presentation to the research clinic.…”
Section: Methodsmentioning
confidence: 99%
“…During middle and high school, executive functioning deficits (i.e., organization, time management, and planning problems; Barkley et al 2001) are the most consistently identified mechanisms of ADHD-related academic failure (Langberg et al 2013; Rogers et al 2011; Sibley et al 2014a). At the transition to middle school, the academic environment becomes increasingly complex as students must independently transition between classes with separate teachers, keep track of assigned work and deadlines, and complete multistep academic tasks and projects (Eccles 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation